2011
DOI: 10.1117/12.876535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iron oxide nanoparticle and microwave hyperthermia alone or combined with cisplatinum in murine breast tumors

Abstract: Surgery, radiation and chemotherapy are currently the most commonly used cancer therapies. Hyperthermia has been shown to work effectively with radiation and chemotherapy cancer treatments. The major obstacle faced by previous hyperthermia techniques has been the inability to deliver heat to the tumor in a precise manner. The ability to deliver cytotoxic hyperthermia to tumors (from within individual cells) via iron oxide magnetic nanoparticles (mNP) is a promising new technology that has the ability to greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, evidence suggests that hyperthermia can be effective in improving flow throughout these tumors that can overcome some of the biological barriers to delivery when significant localized heating is achieved. Increases in blood flow and accumulation have been observed both during and after hyperthermia (Khandhar et al, ; Petryk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence suggests that hyperthermia can be effective in improving flow throughout these tumors that can overcome some of the biological barriers to delivery when significant localized heating is achieved. Increases in blood flow and accumulation have been observed both during and after hyperthermia (Khandhar et al, ; Petryk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…121 Sensitivity of the tumor cells to hyperthermia depends on several factors such as pH, oxygen concentration and cell nutrient level. 122 Preclinical trials have demonstrated that combination of hyperthermia with chemotherapy have enhanced cytotoxicity on tumor cells. 123 Iron oxide NPs with ligands can be utilized in case of specic types of breast cancer for targeted hyperthermia therapy or injected into the tumor tissues for nonspecic hyperthermia.…”
Section: Applications Of Metal Oxide Nanoparticle For Overcoming Mdr ...mentioning
confidence: 99%
“…The investigation demonstrated that magnetic nanoparticle-based hyperthermia therapy has improved signicantly over conventional hyperthermia treatments. 122 The SPION (e.g., MF66) were electrostatically conjugated with either Nucant multivalent pseudopeptide (N6L; MF66-N6L), doxorubicin (DOX; MF66-DOX) or both (MF66-N6L-DOX). Cytotoxicity of these drugs was examined utilizing MDA-MB-231 breast tumor cells, whereas healing efficiency was examined with subcutaneous MDA-MB-231, TNBC tumor in mice.…”
Section: Applications Of Metal Oxide Nanoparticle For Overcoming Mdr ...mentioning
confidence: 99%
“…Magnetic nanoparticles allow the supply of tumor-specific hyperthermia intracellularly at the nanoscale level [134]. This can greatly improve the therapeutic efficacy of hyperthermia, concentrating the particles in the tumor and achieving better homogeneity [135]. An alternating magnetic field (AMF) is then applied, heating tumor cells to eradicate/damage cancerous cells.…”
Section: Hyperthermic Therapymentioning
confidence: 99%